Pipeline Integrity Management Systems : a Practical Approach - Mora, Rafael G.; Hopkins, Phil; Cote, Edgar I.; Shie, Taylor (The American Society of Mechanical Engineers, 2016)
The key for success of Pipeline Integrity Management resides in the dynamic linkage and interaction between a management system (MS) and an Integrity Management Program (IMP), known as Pipeline Integrity Management System (PIMS), for continuously improving pipeline integrity and sustaining risk reduction. This approach enables organizations to obtain adequacy/completeness, timely implementation, and effectiveness to achieve integrity goals, objectives, and targets towards the safety of employees and the public, the protection of the environment, and maintaining reliable service. The contents of this book follow the PIMS process having each applicable chapter use a PLAN-DO-CHECK-ACT (PDCA) process, multiple examples from authors? experiences, and several graphs and tables. This is intended to make it easier for the reader to become the Hero of the Pipeline Integrity Story.
Title from PDF title page (ASME eBooks Web site, viewed on January 11, 2017).
Keywords: Petroleum pipelines -- Safety measures.; Petroleum pipelines -- Reliability.; Petroleum pipelines -- Inspection.; Petroleum industry and trade -- Risk management.; elektronické knihy; electronic books